2020
DOI: 10.1140/epjc/s10052-020-7667-6
|View full text |Cite
|
Sign up to set email alerts
|

FCNC transitions of $$\Lambda _b$$ to neutron in Bethe–Salpeter equation approach

Abstract: In a covariant quark-diquark model, we investigate the rare decay of Λ b → nl + l − and Λ b → nγ in the Bethe-Salpeter equation approach. In this model the baryons are treated as bound states of a constituent quark and a diquark interacting via a gluon exchange and the linear confinement. We find that the ratio of form factors R is varies from −0.90 to −0.25 and the branching ratios Br(Λ b → nl + l − ) × 10 8 are 6.79(l = e), 4.08 (l = µ), 2.9 (l = τ ) and the branching ratio Br(Λ b → γ) × 10 7 ) = 3.69 in cen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 68 publications
1
13
0
Order By: Relevance
“…To check our results in the LFQM, we would also like to study the decays Our results of the branching ratios from the LFQM and SU(3) F are given in Table IV, where we have also shown the SU(3) F evaluations in Ref. [22] and some of other theoretical predictions in the literature, such as LCSR [23,24], BSE [25] and QM [27,29], as well as the current experimental data [15,16]. In particular, for b → sγ in the LFQM approach, we find that B(Λ b → Λγ) = (7.1 ± 0.3) × 10 −6 , which agrees well with the experimental measured value.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To check our results in the LFQM, we would also like to study the decays Our results of the branching ratios from the LFQM and SU(3) F are given in Table IV, where we have also shown the SU(3) F evaluations in Ref. [22] and some of other theoretical predictions in the literature, such as LCSR [23,24], BSE [25] and QM [27,29], as well as the current experimental data [15,16]. In particular, for b → sγ in the LFQM approach, we find that B(Λ b → Λγ) = (7.1 ± 0.3) × 10 −6 , which agrees well with the experimental measured value.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…In addition, our LFQM results in b → sγ agree well with both the predictions given by SU(3) F and Refs. [23][24][25]. Note that the values based on SU(3) F in Ref.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of the application of LS and BS equations on the hadron physics could be found in Refs. [169,170,171,172], etc.. A typical BS integration equation reads…”
Section: Lippmann-schwinger and Bethe-salpeter Equationsmentioning
confidence: 99%
“…[27], we can estimate the value of R and observe that it changes from to , which is not a constant. In our previous studies [28,29], we observed that the ratio R is not a constant in the rare decay in a large momentum region in which we did not consider the long distance contributions because they have a small effect on the FFs of this decay [30,31]. In these studies, (Λ) was considered a bound state of two particles: a quark and a scalar diquark.…”
Section: Introductionmentioning
confidence: 99%